The manufacturers’ strategy selection of carbon emission reduction and pricing under carbon trading policy and consumer environmental awareness - Dai, Yao; Wu, Hongliang; Pan, Helin; Luo, Lijian (Frontiers in Environmental Science, 2023)
Carbon trading policy and consumer environmental awareness are more and more important to manufacturers’ carbon emission reduction and pricing. To analyse their strategy selection of carbon emission reduction and pricing, this paper develops three game models, where two manufacturers could choose no cooperation (NC), only cooperation in carbon emission reduction (SC) or simultaneous cooperation in carbon emission reduction and pricing (CC). By solving these models and comparing their environmental R&D levels, net carbon emissions and profits, the paper finds strategy selection for manufacturers and its conditions. Results show that from the view of environmental R&D level and supply chain's profit, NC and SC may be the optimal strategy and the second-best strategy respectively. From the net carbon emissions point of view, CC and SC should be the optimal strategy and the second-best strategy respectively. As to manufacturers' profits, CC should be the optimal strategy, and NC or SC should be the second-best strategy. From comprehensive views, none of these strategies could be the optimal strategy, but SC may be the second-best strategy. This paper makes contributions in three aspects. First, this paper designs three strategies of carbon emission reduction and pricing for two manufacturers. Second, this paper takes the initial carbon emission allowances of the government as one of decision variables. Finally, this paper investigates effects of different strategies and finds strategy selections for manufacturers from a single view and comprehensive views.